Solid amine low-temperature carbon capture material adsorbent and preparation method thereof
By using AMP-modified TEPA-LDH-derived MMO materials to regulate their chemical composition and structure, the problem of degradation of CO2 adsorption performance in multiple uses of solid amine materials is solved, and efficient CO2 capture and multiple cycle stability is achieved at low temperatures, which promotes the large-scale application of solid amine low-temperature carbon capture technology.
Patent Information
- Application Number
- CN202410958368.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-03-28
AI Technical Summary
During the multiple use of existing solid amine low-temperature carbon capture materials, amine groups are prone to leaching, resulting in a decrease in CO2 adsorption performance and high preparation cost, which limits its large-scale application.
A solid amine low-temperature carbon capture material with excellent CO2 adsorption performance and high stability was prepared by regulating the load ratio of AMP and TEPA and the molar ratio of divalent/trivalent metals.
It has achieved excellent CO2 adsorption capacity under low temperature conditions and maintained high stability in multiple adsorption-desorption cycles, reducing the preparation cost of materials and promoting the large-scale application of solid amine low-temperature carbon capture technology.
Smart Images

Figure CN119701876A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid amine low-temperature carbon capture material adsorbent and a preparation method thereof. Background Art
[0002] Carbon dioxide is one of the main components of greenhouse gases, and its excessive emission is one of the main causes of global warming. Carbon capture and storage technology is a technology that reduces CO 2 However, CO in the air is one of the most effective means of emission. 2 The concentration is relatively low, usually about 400 ppm, which makes the adsorbent face the problem of low adsorption capacity in practical applications. Therefore, it becomes particularly important to develop a material with high adsorption capacity.
[0003] Solid amine materials have become the most promising low-temperature carbon capture technology due to their low energy consumption, low corrosion, high adsorption capacity, and good regeneration performance. However, during repeated use of solid amine materials, the amine groups are easily leached, resulting in CO 2 The adsorption performance is reduced and the preparation cost of high-performance solid amine materials is high, which limits their large-scale application. In addition, the performance of solid amine adsorbents is greatly affected by the carrier structure. In particular, the pore structure of the carrier plays an important role in the adsorption capacity and adsorption rate. Carriers with large pore size and high pore volume can provide more active sites, which helps to improve the CO absorption capacity of the adsorbent. 2 Capture performance. In order to further improve the performance of solid amine adsorbents, introducing appropriate additives for modification is also one of the key strategies. Additives can improve the overall performance of the adsorbent through various mechanisms, such as increasing adsorption sites, improving the distribution of amine groups, and enhancing the stability of the adsorbent. Therefore, it is crucial to synthesize a porous material with a large pore volume / diameter that can bind to organic amine groups through strong forces for the large-scale application of solid amine low-temperature carbon capture technology.
[0004] In conclusion, solid amine low-temperature carbon capture technology has reached a high level of technical maturity and has broad application prospects, but it still has a long way to go before large-scale development and application. There is still a lot of room for improvement in the research and development of solid amine materials. 2 Inexpensive adsorbents with high adsorption capacity, fast adsorption kinetics, and good adsorption-desorption stability are crucial for large-scale deployment of industrial decarbonization processes. Summary of the invention
[0005] The object of the present invention is to provide a solid amine low-temperature carbon capture material, which has excellent low-temperature carbon capture performance and can maintain high stability in multiple adsorption-desorption cycles.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A solid amine low-temperature carbon capture material, whose chemical composition system is a 2-amino-2-methyl-1-propanol (AMP) modified tetraethylenepentamine (TEPA)-LDH derived mixed metal oxide (MMO) material, wherein the chemical composition of the material is xAMP-yTEPA-AzB-C-MMO, wherein x and y represent the mass fractions of AMP and TEPA in the total mass of the adsorbent, respectively, A and B are divalent and trivalent metal elements constituting hydrotalcite-like lamellae, C is an interlayer anion, z is the molar ratio of divalent and trivalent metal elements, x is 10-30%wt%, y is 30-70wt%, and z is 0.5-4.
[0008] The solid amine low temperature carbon capture material is characterized in that A in the chemical composition AxB-C of the hydrotalcite-like material can be Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Mn 2+ , Fe 2+ At least one of the following, B may be Al 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C can be CO 3 2- , NO 3- , SO 4 2- , Cl - , OH - , P.O. 4 3- At least one of them.
[0009] The solid amine low temperature carbon capture material, x is 10wt%, y is 60wt%, z is 0.5, and the chemical composition is 10AMP-60TEPA-Mg 0.5 Ga MMO.
[0010] The preparation method of the catalyst comprises the following steps: (1) mixing AMP and TEPA in an organic solvent to prepare a functionalized amine solution; (2) adding MMO to the functionalized amine solution, stirring and mixing at room temperature, and obtaining the xAMP-yTEPA-AzB-C-MMO solid amine low-temperature carbon capture material after vacuum drying.
[0011] The preparation method of MMO comprises the following steps: (1) mixing two or more precursor substances containing A and B respectively to form a precursor solution; (2) adding the precursor solution to an alkaline solution to obtain a mixed solution, controlling its pH value, and aging it; (3) filtering and washing the aged mixed solution in deionized water and an organic solvent in succession, and then vacuum drying to obtain a hydrotalcite-like material containing A and B; (4) fully grinding the obtained hydrotalcite-like material containing A and B, and calcining it in a tubular furnace to obtain a mixed metal oxide containing A and B.
[0012] In the MMO preparation method, the pH value of the mixed solution in step (2) is controlled within the range of 9 to 12, more preferably within the range of 9.5 to 10.5, and the aging time is more than 10 hours.
[0013] In the MMO preparation method, the organic solvent in step (3) is specifically at least one of methanol, ethanol and acetone, the vacuum drying temperature is 60° C., and the vacuum degree is -0.1 to 0 MPa.
[0014] The MMO preparation method, wherein the calcination conditions in step (4) are 300-500°C, N 2 Calcinate in atmosphere for 3 to 6 hours.
[0015] The solid amine low temperature carbon capture material can be used in the CO2 capture temperature range of 25 to 85°C. 2 The concentration range may be 0.04% to 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 N of MgxGa-MMO solid amine carbon capture materials with different A / B molar ratios prepared by the present invention 2 Adsorption-desorption isotherms and pore size distribution diagram.
[0017] Figure 2 CO2 capture of xAMP-yTEPA-AzB-MMO solid amine carbon capture materials with different AMP and TEPA loadings (10-30 wt%) prepared by the present invention 2 Adsorption
[0018] Figure 3 CO2 capture of yTEPA-AzB-MMO solid amine carbon capture materials with different TEPA loadings (10-30 wt%) prepared by the present invention 2 Adsorption
[0019] Figure 4 10AMP-60TEPA-Mg prepared by the present invention 0.5Comparison of the adsorption-desorption cycle performance of Ga-MMO solid-state amine carbon capture materials. DETAILED DESCRIPTION
[0020] The present invention provides a solid amine low-temperature carbon capture material and its preparation and application, which has excellent CO 2 The present invention uses 2-amino-2-methyl-1-propanol to functionalize TEPA, then adds magnesium-gallium mixed metal oxide, and prepares a series of organic amine-mixed metal oxide composite solid materials by adjusting the amine loading ratio and the molar ratio of divalent / trivalent metals, and conducts low-temperature CO 2 The adsorption performance was tested. The adsorbent of the specific example is 10AMP-60TEPA-Mg 0.5 Take Ga MMO as an example.
[0021] Example 1. AxB-C-MMO adsorbents with different Mg / Ga molar ratios (0-5)
[0022] (1)Mg 0.5 Preparation method of Ga-MMO (coprecipitation method)
[0023] 8.547 g Mg(NO 3 ) 2 6H 2 O and 17.049g Ga(NO 3 ) 3 Dissolve in 100 ml of deionized water to obtain a stable, transparent mixed solution. At room temperature, add the mixed solution dropwise to a solution containing 5.299 g of Na 2 CO 3 100mL solution was added, and 4mol / L NaOH solution was used to keep the pH value of the mixed solution at about 10.0. After the obtained mixed solution was aged at room temperature for 12h, it was repeatedly washed with deionized water until the pH value of the filtrate was 7.0. When the filtrate was almost dried, it was washed with ethanol 1 to 2 times and dried to obtain a precipitate. The obtained sample was dried in a vacuum drying oven at 60℃ for 12h to obtain Mg 0.5 Ga-CO 3 LDHs, LDH powder was fully ground and placed in a tube furnace at 450 °C, N 2 Mg was successfully prepared by calcining for 5 h under atmosphere. 0.5 Ga MMO.
[0024] Mg 1 The preparation method of Ga MMO adsorbent is similar to that of Mg in Example 1. 0.5 The preparation method of Ga-MMO material is different in that 12.82g Mg(NO3 ) 2 6H 2 O and 12.79g Ga(NO 3 ) 3 Dissolve in 100 mL of deionized water.
[0025] Mg 2 The preparation method of Ga MMO adsorbent is similar to that of Mg in Example 1. 0.5 The preparation method of Ga-MMO material is different in that 17.10 g Mg(NO 3 ) 2 6H 2 O and 8.53g Ga(NO 3 ) 3 Dissolve in 100 mL of deionized water.
[0026] Mg 3 The preparation method of Ga MMO adsorbent is similar to that of Mg in Example 1. 0.5 The preparation method of Ga-MMO material is different in that 19.23g Mg(NO 3 ) 2 6H 2 O and 6.39g Ga(NO 3 ) 3 Dissolve in 100 mL of deionized water.
[0027] Mg 4 The preparation method of Ga MMO adsorbent is similar to that of Mg in Example 1. 0.5 The preparation method of Ga-MMO material is different in that 20.51g Mg(NO 3 ) 2 6H 2 O and 5.12g Ga(NO 3 ) 3 Dissolve in 100 mL of deionized water.
[0028] (2) Specific surface area analysis
[0029] The specific surface area and pore structure characteristics of the synthesized sample powder were analyzed using BET (SSA-7000) technology. x BC-MMO was pretreated at 220°C for 5 h. The Barrett-Joyner-Halenda (BJH) method was used to analyze A x Pore size distribution, pore volume and N of BC-MMO 2 Adsorption-desorption curve. Results ( Figure 1 and Table 1) show that the material presents a classic type IV isothermal adsorption-desorption curve, and a typical hysteresis loop appears in the relative pressure range of 0.5 to 1, indicating that Ax BC-MMO both show mesoporous structure. Mg 0.5 GaLDO has a higher pore volume and pore size, which can accommodate more amines and make the active sites of amines more dispersed, which is beneficial to CO 2 Diffusion in the pores, with higher CO 2 Adsorption capacity and faster adsorption speed.
[0030] Table 1Mg 0.5 Specific surface area, pore volume and pore size of Ga-MMO adsorbent
[0031] sample <![CDATA[Specific surface area (m 2 ·g -1 )]]> <![CDATA[BJH pore volume (cm 3 ·g -1 )]]> BJH aperture(A) <![CDATA[Mg 0.5 GaMMO]]> 172.2 1.06 123.4 <![CDATA[Mg 1 GaMMO]]> 228.4 1.39 122.1 <![CDATA[Mg 2 GaMMO]]> 259.6 1.44 110.7 <![CDATA[Mg 3 GaMMO]]> 330.3 2.12 128.5 <![CDATA[Mg 4 GaMMO]]> 267.5 1.59 118.9
[0032] Example 2. yTEPA-A with different TEPA loadings (30-70 wt%) z B-MMO adsorbent
[0033] (1) 60TEPA-Mg 0.5 Preparation method of Ga-MMO adsorbent (impregnation method)
[0034] 0.75 g of tetraethylenepentamine was dissolved in 30 mL of methanol solution and heated under N 2 The mixture was stirred magnetically for 1 h (600 rpm) under atmosphere; 0.50 g of dry Mg 0.5 Ga MMO powder was added to the above mixed solution and 2 The mixture was stirred for 3 h (600 rpm) under the atmosphere; the resulting solution was placed in a 60°C water bath and the methanol solvent was removed using a rotary evaporator at -0.1 MPa. The remaining solid adsorbent powder was collected and placed in a 60°C vacuum drying oven for overnight drying to obtain the final sample 60TEPA-Mg 0.5 Ga-MMO.
[0035] 30TEPA-Mg 0.5 Preparation method of Ga-MMO adsorbent is similar to that of 60TEPA-Mg in Example 2 0.5 The difference in the preparation method of GaMMO material is that 0.22 g of tetraethylenepentamine is placed in 30 mL of methanol solution.
[0036] 40TEPA-Mg 0.5 Preparation method of Ga-MMO adsorbent is similar to that of 60TEPA-Mg in Example 2 0.5 The preparation method of Ga MMO material is different in that 0.34 g of tetraethylenepentamine is placed in 30 mL of methanol solution.
[0037] 50TEPA-Mg 0.5 Preparation method of Ga-MMO adsorbent is similar to that of 60TEPA-Mg in Example 20.5 The difference between the preparation methods of Ga MMO materials is that 0.50 g of tetraethylenepentamine is placed in 30 mL of methanol solution.
[0038] 70TEPA-Mg 0.5 Preparation method of Ga-MMO adsorbent is similar to that of 60TEPA-Mg in Example 2 0.5 The preparation method of Ga MMO material is different in that 1.15 g of tetraethylenepentamine is placed in 30 mL of methanol solution.
[0039] (2) CO of adsorbent 2 Adsorption capacity test method
[0040] CO 2 The adsorption performance test was carried out in a Q50 TA Instruments Q500 thermogravimetric analyzer (TGA). Approximately 10 mg of the adsorbent was placed in a crucible of the thermogravimetric analyzer and the adsorbent was heated at 25 °C and 400 ppm CO. 2 The above CO 2 Adsorption performance test method for determination of yTEPA-A z CO2 adsorbent of B-MMO 2 The test results (as shown in Table 2) show that the TEPA loading capacity has a significant effect on the adsorption capacity of yTEPA-A. z CO2 adsorbent of B-MMO 2 The adsorption performance is greatly affected. Initially, the adsorption capacity of the material increases with the increase of TEPA loading. Higher TEPA loading provides more adsorption sites. When the TEPA loading is 60wt%, the adsorption capacity of the adsorbent is the highest, reaching 3.19mmol g -1 When the TEPA loading was further increased to 70wt%, excessive amine accumulation caused the pores of the material to be blocked, and the adsorption capacity of the adsorbent decreased.
[0041] Table 2 Effect of different TEPA loading amounts on yTEPA-A z BC-MMO adsorbent CO 2 Adsorption capacity test (adsorption temperature is 75℃, CO 2 Concentration 10%)
[0042] TEPA loading (wt%) 30 40 50 60 70 <![CDATA[CO 2 Adsorption capacity (mmolg -1 )]]> 1.44 2.14 2.79 3.19 2.18
[0043] Example 3. Effect of AMP loading on CO 2 Effect of adsorption performance
[0044] (1)10AMP-60TEPA-Mg 0.5 Preparation method of Ga-MMO (impregnation method)
[0045] 10AMP-60TEPA-Mg 0.5 Preparation method of Ga MMO adsorbent is similar to that of 70TEPA-Mg in Example 2 0.5 The preparation method of Ga-MMO material is different in that the total organic loading is kept unchanged at 70wt%, and 0.16g of 2-amino-2-methyl-1-propanol and 0.99g of tetraethylenepentamine are added to 30mL of methanol solution.
[0046] 20AMP-50TEPA-Mg 0.5 Preparation method of Ga MMO adsorbent is similar to that of 70TEPA-Mg in Example 2 0.5 The preparation method of Ga-MMO material is different in that the total organic loading is kept unchanged at 70wt%, and 0.33g of 2-amino-2-methyl-1-propanol and 0.84g of tetraethylenepentamine are added to 30mL of methanol solution.
[0047] 30AMP-40TEPA-Mg 0.5 Preparation method of Ga MMO adsorbent is similar to that of 70TEPA-Mg in Example 2 0.5 The preparation method of Ga-MMO material is different in that the total organic loading is kept unchanged at 70wt%, and 0.5g of 2-amino-2-methyl-1-propanol and 0.67g of tetraethylenepentamine are added to 30mL of methanol solution.
[0048] Using CO in Example 2 2 Adsorption capacity test method for xAMP-yTEPA-A z The CO2 adsorption capacity of B-MMO adsorbent. The test results (as shown in Table 3) show that the optimal CO2 adsorption capacity is obtained when the AMP and TEPA loadings are 10 wt% and 60 wt%, respectively. 2 Adsorption performance 3.45mmol g -1 It is proved that after AMP functionalization, the distribution of TEPA molecules on the surface and pores of MMO carriers is more uniform, which increases the accessibility of adsorption sites and makes CO 2 It is easier to diffuse into the adsorbent, thereby increasing the CO 2 Adsorption amount.
[0049] Table 3 Effect of different AMP and TEPA loading on xAMP-yTEPA-A z B-MMO adsorbent CO 2 Adsorption capacity test (adsorption temperature is 75℃, CO 2 Concentration 10%)
[0050] AMP loading (wt%) 10 20 30 TEPA loading (wt%) 60 50 40 <![CDATA[CO 2 Adsorption capacity (mmolg -1 )]]> 3.45 3.28 3.10
[0051] (2) Adsorption-desorption cycle performance test of solid amine materials
[0052] The CO of different samples was measured using a Q500 thermogravimetric analyzer (TGA). 2 Adsorption-desorption cycle performance. Weigh about 10 mg of sample and test it at 25°C and 400 ppm CO 2 / N 2 The adsorption lasted for 360 min under the conditions, and then the temperature was raised to 100 °C and the adsorption was carried out under high purity N 2 The atmosphere desorption was performed for 15 minutes, which was considered as one cycle, and so on. The test results of the cyclic performance (Table 4) showed that 10AMP-60TEPA-Mg 0.5 Ga MMO adsorbent has good adsorption-desorption cycle stability. It is proved that AMP functionalization and the excellent pore structure of MMO carrier can significantly improve the thermal stability and chemical stability of the adsorbent, enhance its regeneration performance during the adsorption-desorption cycle, and ensure that the adsorption capacity after multiple cycles remains at a high level.
[0053] Table 4xAMP-yTEPA-A z CO2 adsorbent of BC-MMO 2 Absorption-desorption cycle performance
[0054] <![CDATA[First cycle adsorption capacity (mmol g -1 )]]> 3.47 <![CDATA[The 5th cycle adsorption capacity (mmol / g) -1 )]]> 3.03 Performance loss in 5 cycles (%) 12.6
[0055] Based on the above experimental results, we get:
[0056] For xAMP-yTEPA-A z BC-MMO adsorbent, when A and B are Mg 2+ , Ga 3+ , x = 10 ~ 30wt%, y = 30 ~ 70wt%, z = 0.5 ~ 4, at 10% CO 2 , low temperature (25~85℃) conditions have higher CO 2 Adsorption capacity, when x is 10wt%, y is 60wt%, and z is 0.5, at an adsorption temperature of 75℃ and CO 2 At a concentration of 10%, 3.45 mmol g -1 The highest adsorption capacity of 2-amino-2-methyl-1-propanol-modified tetraethylenepentamine-LDH-derived mixed metal oxide (MMO) adsorbent was obtained and maintained high stability during 5 adsorption-desorption cycles with a performance loss of only 12.6%, demonstrating that the 2-amino-2-methyl-1-propanol-modified tetraethylenepentamine-LDH-derived mixed metal oxide (MMO) adsorbent has excellent CO absorption performance at low temperatures. 2 Adsorption performance.
[0057] Based on the above experimental results, the inventors also conducted further experiments on the composition and molar fraction of each element in the adsorbent. The experimental results show that:
[0058] Ensures high CO at low temperatures 2 The chemical composition of the catalyst of the present invention can be expressed as xAMP-yTEPA-A z BC-MMO, where x and y represent the mass fraction of the two types of organic amines in the total mass of the adsorbent, x is 10-30%wt%, y is 30-70wt%, and A can be Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ , Fe 2+ At least one of the following, B may be Al 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C can be CO 3 2- , NO 3 - , SO 4 2- , Cl - , OH - , P.O. 4 3- At least one of the following. The preferred adsorbents are as follows: preferably x is 10wt%, y is 60wt%, A is Mg 2+ , B is Ga 3+ , C is CO 3 2- , x is 0.5, the preferred chemical composition is 10AMP-60TEPA-Mg 0.5 Ga-MMO.
[0059] In addition, other parameters in the preparation method can also be adjusted. For example, the organic solvent is specifically at least one of anhydrous methanol, anhydrous ethanol and acetone; the pH value of the mixed solution in step (2) is controlled in the range of 8 to 12, more preferably in the range of 9.5 to 10.5; the vacuum drying temperature is 25°C to 120°C, and the vacuum degree is -0.1 to 0 MPa; the water bath temperature of the rotary evaporator is set to 25°C to 80°C, the rotation speed is 10 to 100 rpm, and the vacuum degree is -0.1 to 0 MPa.
[0060] The adsorbent prepared by the present invention is applied to CO 2The capture temperature range is 25-85°C, and the captured CO 2 The concentration range may be 0.04% to 100%.
Claims
1. A solid amine low temperature carbon capture material, whose chemical composition system is a 2-amino-2-methyl-1-propanol (AMP) modified tetraethylenepentamine (TEPA)-LDH derived mixed metal oxide (MMO) material, the chemical composition of the material is xAMP-yTEPA-AzB-C-MMO, wherein, x, y represent the mass fraction of AMP and TEPA in the total mass of the adsorbent, A, B are the divalent and trivalent metal elements constituting the hydrotalcite-like layers, C is the interlayer anion, z is the molar ratio of the divalent and trivalent metal elements, x is 10-30%wt%, y is 30-70wt%, and z is 0.5-4.
2. The solid amine low temperature carbon capture material according to claim 1, wherein x is 10wt%, y is 60wt%, z is 0.5, and the chemical composition is 10AMP-60TEPA-Mg 0.5 GaMMO.
3. The method for preparing the solid amine low-temperature carbon capture material according to claim 1, comprising the following steps: (1) AMP and TEPA are mixed in an organic solvent to prepare a functionalized amine solution; (2) MMO is added to the functionalized amine solution, stirred and mixed at room temperature, and vacuum dried to obtain the xAMP-yTEPA-AzB-C-MMO solid amine low-temperature carbon capture material.
4. The method for preparing a solid amine low-temperature carbon capture material according to claim 3, wherein the organic solvent is at least one of methanol, ethanol, and acetone, the vacuum drying temperature is 60°C, and the vacuum degree is -0.1 to 0 MPa.
5. The method for preparing the solid amine low-temperature carbon capture material according to claim 1, wherein the method for preparing MMO comprises the following steps: (1) mixing two or more precursor materials containing A and B respectively to form a precursor solution; (2) adding the precursor solution to an alkaline solution to obtain a mixed solution, controlling the pH value thereof, and aging the mixed solution; (3) The aged mixed solution is filtered and washed in deionized water and an organic solvent, and then vacuum dried to obtain a hydrotalcite-like material containing A and B; (4) The obtained hydrotalcite-like material containing A and B is fully ground and calcined in a tubular furnace to obtain a mixed metal oxide containing A and B.
6. The pH value of the mixed solution in step (2) is controlled within the range of 9 to 12, more preferably within the range of 9.5 to 10.
5. The solid amine low-temperature carbon capture material according to claim 5 is characterized in that: The A in the chemical composition AxB-C of the hydrotalcite-like material may be Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Mn 2+ , Fe 2+ At least one of the following, B may be Al 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C can be CO3 2- , NO 3- , SO4 2- , Cl - , OH - ,PO4 3- At least one of them.
7. The preparation method according to claim 5, wherein the aging time is 6 to 24 hours.
8. The preparation method according to claim 5, wherein the calcination conditions in step (4) are calcination at 300-500°C in a N2 atmosphere for 3-6 hours.
9. The solid amine low-temperature carbon capture material according to claim 1, wherein the temperature range for CO2 capture can be 25 to 85°C, and the captured CO2 concentration range can be 0.04% to 100%.